'Cartoonish lumps': the surface appeal of Alison Bechdel's Are You My Mother?". Issue 1 (2nd January 2018) - Camden, Vera J.
ABSTRACT: A reviewer for The Wall Street Journal dismisses what he calls the 'cartoonish lumps' of the Medieval St. Albans figures at the Getty Center. He accuses the artist of childishness: as if the artist did not yet know, developmentally, how to draw. 'Their creators hadn't yet figured out how to make human beings look human. Their faces are expressionless and dumb (eyes are white circles with black dots in the middle) … Their attenuated bodies … are devoid of musculature or fat'. Such a critique defends against the amplified affective states conjured by these images. Drawing on psychoanalyst Didier Anzieu's theories of the 'skin-ego' and surface, this article reflects upon the childlike 'simplicity' of the lines shared by these 'cartoonish' figures, and the bold, spare lines of Alison Bechdel's graphic narratives. Bechdel summons affective regions conjured by the flattened surface of the seeming two-dimensional figures, layered against bubbled, staccato scripts. The childlike simplicity of Bechdel's renderings of the human figure allows an affective resonance and, ironically, a longing for the transcendent, enigmatic, and impenetrable realm invoked by the gaze of the Medieval figure.